2015
DOI: 10.1039/c5nr04465k
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional role of trialkylbenzenes for the preparation of aqueous colloidal mesostructured/mesoporous silica nanoparticles with controlled pore size, particle diameter, and morphology

Abstract: Both the pore size and particle diameter of aqueous colloidal mesostructured/mesoporous silica nanoparticles (CMSS/CMPS) derived from tetrapropoxysilane were effectively and easily controlled by the addition of trialkylbenzenes (TAB). Aqueous highly dispersed CMPS with large pores were successfully obtained through removal of surfactants and TAB by a dialysis process. The pore size (from 4 nm to 8 nm) and particle diameter (from 50 nm to 380 nm) were more effectively enlarged by the addition of 1,3,5-triisopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 95 publications
(124 reference statements)
2
26
0
Order By: Relevance
“…Modified Stöber processes, in which TEOS is continuously added to seeds in a growth solution, allow for the growth of large, monodisperse NPs in a single step, provided the seed NPs are well dispersed in the growth solution [28,29]. A versatile approach for growing silica shells onto inorganic NPs that cannot be dispersed in polar media is the reverse microemulsion technique [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In a reverse microemulsion, the aqueous solution is confined in uniform, nanosized droplets that are stabilized by a surfactant such as a polyoxyethylene (5) nonylphenylether (trade name Igepal ® CO-520) and distributed in the continuous nonpolar phase [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified Stöber processes, in which TEOS is continuously added to seeds in a growth solution, allow for the growth of large, monodisperse NPs in a single step, provided the seed NPs are well dispersed in the growth solution [28,29]. A versatile approach for growing silica shells onto inorganic NPs that cannot be dispersed in polar media is the reverse microemulsion technique [22,23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In a reverse microemulsion, the aqueous solution is confined in uniform, nanosized droplets that are stabilized by a surfactant such as a polyoxyethylene (5) nonylphenylether (trade name Igepal ® CO-520) and distributed in the continuous nonpolar phase [44].…”
Section: Introductionmentioning
confidence: 99%
“…For the polycondensation of precursors such as TEOS, ammonia usually acts as a catalyst [43]. This technique allows for the formation of uniform silica shells on individual particle cores [23,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…339 On the other hand, we used triisopropylbenzene as a swelling agent instead of trimethylbenzene. 346 We found that this swelling agent has a stronger ability to cause the swelling of the surfactant micelles.…”
Section: Soft Template;mentioning
confidence: 90%
“…Yamada et al. then developed a swelling strategy to synthesize the DFNS family of silica nanospheres by modifying the standard DFNS protocol by replacing urea with triethanolamine . They used various trialkylbenzenes (TABs) as swelling agents or pore expanders, which allowed the hydrophobicity of the reaction medium to be tuned; this affected the hydrolysis rate of the silane precursors and thus the nucleation‐growth step.…”
Section: Synthesis and Mechanism Of Formation Of Dendritic Fibrous Namentioning
confidence: 99%